Isolation of naphthalene degrading bacteria from mangrove soil at Tanjung Lumpur, Kuantan - Hasan, Mohd Saiful Amri; Baharom, Azrin; Mohd Ashaari, Mardiana; Tengku Abdul Hamid, Tengku Haziyamin (IIUM Press, 2025)
Mangrove ecosystem acts as a boundary between terrestrial and marine ecosystems that harbours unique microbial diversity. It provides a unique ecological niche to different microbes which play various functions in nutrient recycling as well as in various other environmental roles. Hazardous polycyclic aromatic hydrocarbon (PAH) compounds such as naphthalene is being released into the environment especially following the age of industrialisation. Naphthalene can serve as the simplest molecule to represent PAHs. Ability to degrade naphthalene indicates the capability of a microorganism to carry out bioremediation involving more complex compounds. In this study, the naphthalene degrading bacteria were isolated from mangrove soil samples collected near the Sungai Kuantan site at Tanjung Lumpur, Kuantan, Pahang. In total of 12 isolates (S1, S2, S4, S5, S6, S7, S8, S9, B1, B2, B3 and B4) were studied. About 11 isolates were successfully identified using API 20E biochemical test with more than 80% score (acceptable), and only 4 isolates were able to be identified using ribosomal rRNA sequencing. The majority of the isolated species were gram negative rod belonging to various Pseudomonas species. From our study, Pseudomonas sp. (6 isolates) is the dominating genus, followed by Shewanella sp. (2 isolates), and a single isolate each from Proteus sp., Vibrio sp., Ralstonia sp., and Aeromonas sp., respectively. Ability to degrade naphthalene as sole carbon source could indicate that these strains as PAHs degraders in which they have potential to be useful in various applications, especially for bioremediation purposes.